2001
DOI: 10.1107/s0909049500018069
|View full text |Cite
|
Sign up to set email alerts
|

Polarized XAFS study of high-temperature phases of NaNbO3

Abstract: Temperature dependence of the Nb displacement relative to the center of oxygen octahedron in NaNbO 3 has been studied by polarized Nb K XAFS. Spectra were measured at two orientations of a single crystalline sample. Room temperature EXAFS data are in a good agreement with earlier X-ray diffraction data: Nb antiferroelectric displacements were found to be orthogonal to the b axis. Analysis of the temperature dependent EXAFS data didn't reveal any abrupt changes of Nb-O distances in the phase transition points. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…The PDD for Nb is nearly Gaussian but anisotropic with larger magnitudes of displacements in the a-b plane. This result is consistent with existing data for the structures of orthorhombic NaNbO3 [30] and KNbO3 [31] , which indicate that the magnitudes of the locally correlated components of Nb displacements in the c-direction that give rise to the (001) diffuse sheets are relatively small. Sectioning the Nb PDD indicates that the maximum probability is near the average position.…”
Section: Local Structure From Rmc Refinementssupporting
confidence: 92%
See 1 more Smart Citation
“…The PDD for Nb is nearly Gaussian but anisotropic with larger magnitudes of displacements in the a-b plane. This result is consistent with existing data for the structures of orthorhombic NaNbO3 [30] and KNbO3 [31] , which indicate that the magnitudes of the locally correlated components of Nb displacements in the c-direction that give rise to the (001) diffuse sheets are relatively small. Sectioning the Nb PDD indicates that the maximum probability is near the average position.…”
Section: Local Structure From Rmc Refinementssupporting
confidence: 92%
“…These local shifts are disordered, with split-site/hollow Bi PDDs. A similar effect exists for Nb which is known to be locally off-centered in the cubic phases of alkaline niobates [30,31] . As mentioned in the Introduction, octahedral rotations mitigate the underbonding of Bi and thus are expected to couple to its displacements.…”
Section: Discussionmentioning
confidence: 71%
“…Extensive studies on the various aspects of phase transitions in NaNbO 3 have been reported using a variety of experimental techniques including X-ray absorption fine structure, [3] transmission electron spectroscopy, [4] electron paramagnetic resonance, [5] nuclear magnetic resonance, [6] etc. Extensive Raman studies combined with X-ray diffraction (XRD) and dielectric measurements confirmed the presence of an incommensurate phase in NaNbO 3 in the temperature interval 410-460 K. [2] Low wavenumber Raman studies on NaNbO 3 single crystal revealed the occurrence of a quasi-elastic peak, and the phase transition was attributed to the order-disorder process due to the relaxation response of Nb ion in the temperature interval 513-713 K. [7] Shen et al, [8] on the basis of the temperature variation of phonon modes during cooling and heating cycles of measurement, suggested that both FE and AFE phases coexist in the temperature range 40-180 K during cooling cycle.…”
Section: Introductionmentioning
confidence: 99%
“…1. Experimental studies of NaNbO 3 using a wide variety of techniques including x-ray and neutron diffraction [8][9][10][11][12][13][14][15] , Raman and infrared spectroscopy [16][17][18][19][20][21] , XAFS 22 , transmission electron microscopy (TEM) 23 , electron paramagnetic resonance (EPR) 24 , nuclear magnetic resonance (NMR) 25 , etc. have been reported and the crystal structure [8][9][10][11][12][13][14][15] , phonon spectrum [16][17][18][19][20][21]26 , dielectric and piezoelectric behavior 4,6,2 6-30 , temperature and pressure driven phase transitions and critical behavior of the order parameter 24,25 studied.…”
mentioning
confidence: 99%